Influence of warm-up duration on physical performance and psychological perceptions in handball players - Romaratezabala, E.; Nakamura, F. Y.; Castillo, D.; Gorostegi-Anduaga, I.; Yanci, J. (Research in Sports Medicine, 2018)
The purpose of the study was to analyse the effect of two warm-up protocols of different duration on physical performance, perceived load and perception of being ready for a match in handball players. Eighteen handball players were randomly divided into two groups (Wup34min, warm-up protocol of 34 min, Wup17min, warm-up protocol of 17 min). Before and after the warm-up protocols, they performed a battery of physical tests and recorded their perception of feeling ready for a match. At the end of the warm-up protocols, all the players evaluated their differentiated perceived effort (dRPE). The results showed that neither of the protocols significantly modified (p > 0.05) the players` physical performance. However, the Wup34min group showed higher values in the differentiated warm-up perceived load (dRPE-WL) (p < 0.01, TE = 0.97-1.27, high) than the Wup17min group. The players with a greater perceived muscular load (RPEMUSC) experienced a greater decrease in their acceleration capacity (r = 0.48-0.49, p < 0.05). In spite of the fact that neither of the warm-up protocols significantly modified the players` physical performance, a greater perceived muscular load may cause a greater decrease in acceleration capacity.